Implementation of Differentiation-Based Learning Media in the Context of Elementary Education in the Islamic Education Curriculum - Mursal Aziz; Dedi Sahputra Napitupulu; Juli Andriyana (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This research is in the discourse of Islamic education and differentiation-based learning innovation, which has so far been more often discussed in the context of general education than applied in religious curriculum, especially at the elementary level. This article aims to explore the implementation of differentiation-based learning media in the Islamic education curriculum at Madrasah Ibtidaiyah Nurul Husna, and its impact on students' learning experiences. This study uses a qualitative approach with a phenomenological method, where data are collected through participatory observation, in-depth interviews with teachers, principals, and students, as well as documentation studies of learning planning and teaching media used. The research location was chosen purposively because this madrasah is known to actively implement innovative learning approaches. The research findings show that the use of differentiated learning media in the madrasah not only improves the understanding of Islamic material cognitively, but also strengthens affective aspects such as empathy and student spirituality. This approach allows teachers to deliver material according to students' readiness, interests, and learning styles, which has a positive impact on learning engagement. The contribution of this paper lies in expanding the concept of differentiation to the realm of elementary religious education, as well as offering a new perspective on the integration of Islamic values ??in differentiated learning. This study confirms the importance of adaptive and inclusive learning strategies in Islamic education. This result is significant because it paves the way for the transformation of religious learning that is more contextual and relevant to the characteristics of students.